2018
DOI: 10.1515/humo-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation in soccer: a systematic review

Abstract: Purpose. The present study aimed to examine the current methods employed to assess anticipation in soccer players as well as to elicit the main findings of recent studies. Methods. The study was carried out in systematic review form and its sample comprised nine scientific papers published in academic journals. Only the studies involving soccer players (professionals and amateurs, except goalkeepers) were included in this review. Results and conclusions. We observed that most of the studies employed video foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…Comparing the indicators of physical development of football players, it can be seen that in these parameters the players of different playing roles are practically no different from each other. The findings differ somewhat from the results of studies by other authors [21], who found that goalkeepers have the greatest weight and body length. These differences with the results of other authors can be explained by the low football experience of the surveyed children and the need to improve the system of distribution of players by function.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Comparing the indicators of physical development of football players, it can be seen that in these parameters the players of different playing roles are practically no different from each other. The findings differ somewhat from the results of studies by other authors [21], who found that goalkeepers have the greatest weight and body length. These differences with the results of other authors can be explained by the low football experience of the surveyed children and the need to improve the system of distribution of players by function.…”
Section: Discussioncontrasting
confidence: 99%
“…Individual approach to the players is necessary at all stages of sports training, includingat 12 and 15 years, since in these age groups there is a qualitative leap in the level of physical development, which is reflected in the indicators of physical and technical fitness [16,17,18]. In basketball, during this period there is a more rigorous distribution of athletes in terms of functions (which are not always clearly defined in athletes at this stage of preparation), their individual playing profile is determined, and therefore this period plays an important role in becoming a high-class athlete [19,20,21]. That is why the pressing issue is to determine the features of physical development, physical and technical preparedness of players of different game roles in these age groups.…”
Section: Introductionmentioning
confidence: 99%
“…12 (p. 2) All factors associated with perceptual and cognitive processes were classified into one domain; perceptual-cognitive functions. Based on the theoretical assumption that the effects between perceptual-cognitive functions and future football performance might be different depending if a general or a football-specific test were used 13 we also coded the data into two subgroups: perceptual-cognitive functions measured in general tests (i.e., tests where the athlete's responses were related to general standardized perceptual-cognitive tests) and perceptual-cognitive functions measured in football-specific tests (i.e., tests where the athlete's responses were related to football-specific questions, video clips or photos) was performed. Another classification we did in relation to the cognitive functions was based on age.…”
Section: Methodsmentioning
confidence: 99%
“…This, in turn, may cause pains and injuries. Gonçalves et al [29] conducted a review of modern research and concluded that most of the studies employed video footage obtained from soccer matches, which were occluded at a given point for study participants to quickly and precisely elicit the positions of opponents, teammates, and the ball, as well as anticipate actions (dribbling, shooting, passing) from surrounding players (teammates and opponents). in addition, the studies compared the performance of players from both high and low competitive levels in anticipation tasks.…”
Section: Introductionmentioning
confidence: 99%